[PP.29.17] HYPERTENSIVE ENCEPHALOPATHY IN A TERIFLUNOMIDE TREATED PATIENT. (September 2017) - Homentcovschi, C.; Siliste, R.; Ianula, R.; Cristescu, C.
Abstract : Objective: One of the challenges of the last years is to take care of patients with complex treatments, including new drugs. Teriflunomide is a pyrimidine synthesis inhibitor, for the tratament of multiple sclerosis. Hypertension is, according to clinical trials, a rare adverse reaction- 4% for the 14 mg/day. Design and method: Case report: We present the case of a 56 years old women with multiple sclerosis- who begun a treatment with teriflunomide (14 mg/day). She was known as having a grade 2 HTA, obesity and hypercholesterolemia and her treatment consisted in telmisartanum, indapamide and atorvastatine. With this treatment the blood pressure was under 130/ 85 mmHg and she was considered with controlled hypertension when the new drug was introduced. After the second dose- the patient experienced, during nighttime, headache and in the third day of treatment she developed a severe headache, with photophobia and vomitig, and in the Emergency Room the blood pressure was 260/130 mmHg. The rest of clinical examination showed: normal pulmonary auscultation and no signs of systemic congestion, a regular cardiac rhytm and tachycardia (120 beats/min), no focal neurological signs or meningeal irritation. She was admitted to the hospital as hypertensive encefalopathy. The blood tests were normal, excepting a total cholesterol above the recommended limits; the ECG- without changes and an echocardiogram - no signs of left ventricular hypertrophy, a normal kinetic and valves, with a mild dyastolic dysfunction. Results: Under treatment with i.v. vasodilatators and supplementation of the oral treatment with a calcium blocker, the patient become asymptomatic and the blood pressure values return to the recommended limits. She was discharged with a new treatment scheme (adding amlodipine 5 mg/day to the previous drugs), and the ambulatory blood pressure measurement, performed 14 days after that, showed a good control of hypertension. Conclusions: New therapies come with new adverse reactions and in everyday patients, which are rather complex, the close followup is mandatory. The useful tratment for Multiple Sclerosis was, in this patient, followed by a rise of the antihypertensive treatment.